EP696 Inoperable pelvic sidewall recurrence of gynecological cancer treated with proton and carbon ion radiotherapy: CNAO preliminary experience. (1st November 2019) - Barcellini, A; Vitolo, V; Lazzari, R; Cobianchi, L; Biffi, R; Facoetti, A; Fiore, MR; Vischioni, B; Iannalfi, A; Mirandola, A; Vai, A; Mastella, E; et al.
Abstract : Introduction/Background: Re-irradiation of local recurrences of gynaecological cancer pose a difficult challenge to Oncologist. For their biological and physical characteristics particle therapy (PT) could be an interesting treatment. Methodology: The aim of the study was to evaluate the feasibility and early clinical outcome in patients (pts) with gynaecological pelvic sidewall recurrence (PSWr). Between May 2014 to December 2018, 10 patients (median age 56) with PSWr within or at the edge of the previously irradiated field were treated using PT. They had recurrence of: cervical (5), endometrial (3), uterine (1) and ovarian (1) cancer. Previous radiotherapy prescription dose ranged from 46 to 59.4 Gy and 5 patients underwent brachytherapy (range: 7–28 Gy).Two patients, with marginal lymph node recurrence, were irradiated with protons with up to a total dose of 25 GyRBE and 51 GyRBE, respectively. The remaining women underwent carbon-ion radiotherapy (median total dose 50.4 GyRBE; range: 36–57) administered in a median number of 12 fractions. Six patients with PSWr received surgical spacer placement by open surgery to keep intestinal tracts apart from the tumour as the distance between tumour and nearest intestinal tracts was not sufficient. No pts received concurrent chemotherapy. Preliminary local control (LC) and toxicity profile (according to CTCAE V4.03 scale) were evaluated. Results: All patients completed the planned treatment and no acute toxicities G>2 were observed. For the evaluable patients, 1 case of intermediate G≥3 toxicity was reported in women received sequential Bevacizumab (BV). For pts with a follow-up ≥3 months, median LC was 7 months (range: 3–14), median MFS was 4.5 months (range: 3–14, 5) and median OS was 7 months (range: 3–14, 5). 1 pt experienced local progression and 4 pts died for systemic progression. Data are still ongoing. Conclusion: For pts with PSWr a PT approach seems to be feasible and our results showed a promising short-term outcome and limited radiation-related side effects. Longer follow-up and large patient accrual are required. Disclosure: Nothing to disclose.